2020
DOI: 10.1055/s-0040-1715550
|View full text |Cite
|
Sign up to set email alerts
|

FEM Analysis Applied to OT Bridge Abutment with Seeger Retention System

Abstract: Objective The purpose of this investigation is to highlight the technical components of a new kind of screw-retained dental implant prosthesis. The hypothesis is whether the OT Bridge (Rhein 83 S.R.L.; Bologna, Italy) system could be applied without secondary screw in the “all-on-four” retention system, thanks to the presence of an internal seeger. Materials and Methods By using engineering device such as finite element method (FEM) and von Mises investigation, it has been studied how the fixed prosthodontics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Only few works have been carried on this system out, and research and predictable protocols are only at the beginning, but the clinical results seem to be promising. However, studies on the follow-up period and the number of cases reported with "all-on-four" rehabilitation using the OT bridge system are limited [22][23][24]. No studies have been proposed to evaluate the influence of removing one or two anterior screws in an "all-on-four" rehabilitation and the stability of this specific system after mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few works have been carried on this system out, and research and predictable protocols are only at the beginning, but the clinical results seem to be promising. However, studies on the follow-up period and the number of cases reported with "all-on-four" rehabilitation using the OT bridge system are limited [22][23][24]. No studies have been proposed to evaluate the influence of removing one or two anterior screws in an "all-on-four" rehabilitation and the stability of this specific system after mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…A possible solution, retaining the benefits of a screw-in prosthesis, may be provided by the OT-Bridge system [16] in the absence of one or two anterior prosthetic screws [23,24]. In this way, the stability of the OT Bridge system is provided by both the posterior screws and the interlocking system between the acetal Seeger, inserted in the extragrade abutment, and the subequatorial region of the OT equator attachments in the anterior region.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note some inherent limitations of FEA studies. 44 45 46 The loading condition in this study was simplified to a single force, and the boundary condition was set to be fixed at specific locations. In addition, because this is an in silico numerical simulation, other limitations from the applied method are present: there is no presence of variations in temperature, pH, loading incidence, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Another benefit of the OT Equator system is its ability to overcome high implant divergency, even in extreme cases over 80 • . The OT Equator system is also available as a public library in most professional CAD software, allowing for digital workflows [25][26][27][28] and planning in advance of the prosthetically-driven implant-supported rehabilitations.…”
Section: Discussionmentioning
confidence: 99%